Population pharmacokinetics of arbekacin in pediatric patients - Nonoyama, Masato; Matsuura, Nobuo; Sunakawa, Keisuke; Kokubun, Hideya; Kimura, Toshimi; Shimada, Shigehiko (Japanese Journal of Chemotherapy, 2003)
Arbekacin sulfate (ABK), an aminoglycoside antibiotic, has been approved for use in pediatric patients, although its precise pharmacokinetics have not been evaluated due to patient growth and development. We analyzed ABK pharmacokinetics in infants and children by a pharmacokinetic analysis program with the Nonlinear Mixed Effects Model (NONMEM) to estimate population pharmacokinetic parameters. Data was collected retrospectively from 37 subjects 2 months to 17 years old, who received ABK on admission to the pediatric ward of Kitasato University Hospital and who underwent therapeutic drug monitoring. Population pharmacokinetic parameters were calculated and pharmacokinetic variation factors of ABK analyzed with clearance (CLABK) and volume of distribution (VdABK) as pharmacokinetic parameters of the 1-compartment model, using ADVAN 1 and TRANS 2 subroutines. A relative deviation model was used to determine of intersubject variance, and an absolute deviation model for intrasubject variance. Blood concentration samples totaled 80. At a mean dosage of 3.5 mg/kg/dose, blood concentration at 1 hour after the start of drip infusion was 1.5 to 23.5 mg/L and the trough concentrations was 0.4 to 2.8 mg/L. The average CLABK for all subjects, obtained in a basic model of NONMEM analysis, was 0.140 ± 0.09 (L/h/kg), and the average VdABK was 0.47±0.16 (L/kg). CLABK depended on serum creatinine (Scr), and CLABK changes due to aging correlated well with logarithmic function. VdABK started gradually decreasing in infants, which correlated well with exponential function, and ended up at 0.3 L/kg in adults. ABK population pharmacokinetic parameters were finally estimated at: CLABK=0.146Ln(wt)÷Scr(L/h), VdABK=(0.334+0.11Age0.536)×wt (L)